ОСНОВНІ МЕТОДИЧНІ РЕКОМЕНДАЦІЇ З ВИКЛАДАННЯ ЗАГАЛЬНОТЕХНІЧНИХ ДИСЦИПЛІН (Педагогіка вищої та середньої школи, 2022)
The article deals with the principal methodical recommendations on the construction and of delivering the course of lectures on general engineering science at the University.